Double Discrimination Towards Black Women in Hidden Figures and Where Hands Touch - Sabrina, Anindhita; Sumbayak, Desri Maria; Nasution, Ely Hayati (Talenta Publisher, 2023)
This research is intended to describe the double discrimination towards black women in society found in Hidden Figures and Where Hands Touch, and to find out the similarities and differences of double discrimination towards black women between the two films. This study used a qualitative descriptive method, which involves gathering, categorizing, and analyzing data. The data were dialogues and scene shots related to double discrimination. Based on the data analysis, there are racial and gender discrimination that is found in internal and external conflicts. After analyzing the data through the analysis of the intrinsic elements, similarities and differences are found between the two films. The two main characters; Katherine and Leyna, were similarly mistreated and harmed by society as black women. Katherine fought against double discrimination, while Leyna could do nothing but surrender. Their races and backgrounds are also different. Katherine was born to black American parents and lived in Virginia, United States. Meanwhile, Leyna was born biracial to black African and white German and lived in Berlin, Germany. In America in 1961, there was still tolerance, even though black women were still distinguished from white women. However, in Germany in 1944, there was no place for black women